Die geheim van die prediking: In-stemming met die gemeente - Cilliers, Johan (HTS teologiese studies, 2002)
The secret of preaching: Tuning in to the congregationThis paper concentrates on the role of the congregation in the process of preaching, contending that true contextualisation can only take place when the congregation fulfills its role as carrier and protector of the truth. It advocates the development of an ecumenical and hermeneutical approach to preaching, which not only implies a dialogue with the congregation of the present, but also of the past. The paper takes a brief look at certain homiletical trends in this regard, and puts forth three contours of contextualisation: (a)the continual translation of the language of Scripture, (b)the contemporary adaptation of the form of preaching, and (c)the nurturing of a congregational-hermeneutical culture.